A Review of Pollutant Concentrations in Urban Stormwater Across Eastern Australia, After 20 Years - Drapper, Darren; Olive, Kent; McAlister, Tony; Coleman, Rhys; Lampard, Jane-Louise (Frontiers in Environmental Chemistry, 2022)
Concerns about pollutants in urban stormwater were initially raised in the United States of America (USA) in the early 1970s. Australian investigations decades later, also found urban stormwater runoff contained elevated levels of sediment, nutrients, and heavy metals. Planning policies implemented in Australia integrated stormwater management into development via water sensitive urban design (WSUD). Since the introduction of these policies, comprehensive field testing of stormwater quality has been limited. This paucity of field data prompted some organisations to initiate their own locally-specific studies. This review collates urban stormwater data from 77 Australian studies, from Melbourne, Victoria, to North Queensland. The raw dataset included concentrations from 2,836 events and 4,536 individual results, collected between 1993 and 2021 from local councils, research organisations and water authorities. The review examined total suspended solids (TSS), total phosphorus (TP) and total nitrogen (TN) concentrations, prior to any treatment measures. Summary statistics of TSS (x ̅ = 101.4  99.8 mg/L), TP (x ̅ = 0.29  0.211 mg/L) and TN (x ̅ = 1.77  0.97 mg/L) were observed for urban residential catchments. For commercial catchments, summary statistics of TSS (x ̅ = 104.2  308.8 mg/L), TP (x ̅ = 0.355  0.797 mg/L) and TN (x ̅ = 1.29  1.35 mg/L) were observed. Industrial catchments were observed with summary data of TSS (x ̅ = 127.1  129.2 mg/L), TP (x ̅ = 0.314  0.234 mg/L) and TN (x ̅ = 1.85  1.549 mg/L). Seminal research, used to inform stormwater management design guidelines and predictive water quality treatment modelling across Australia, is significantly different (p < 0.001). International data is also between 20% - 200% higher. Generalised linear modelling found the geographic location had the greatest influence on concentrations of TSS, TP and TN (p < 0.001). These results emphasise the importance of regular review of urban stormwater quality data as urban planning concepts evolve. Based on the findings of this review, generic load reduction targets (expressed as a percentage of annual inputs), may be sub-optimal. Place-based targets, or ecological and hydrological benchmarks may be a more appropriate tool.